UK owner preferences for treatment of feline injection site sarcomas. (13th December 2013) - Carwardine, D.; Friend, E.; Toscano, M.; Bowlt, K.
<x xml:space="preserve">Abstract</x> OBJECTIVES Feline injection site sarcomas are therapeutically challenging because of their locally invasive nature. Several protocols recommend that the two perceived high‐risk adjuvanted vaccines should be administered into distinct anatomical sites ("left hind leg leukaemia, right hind leg rabies"), which should aid surgical resection. This has resulted in a change in tumour distribution with an increased proportion situated caudal to the diaphragm when such a policy is adopted. The aim of this study was to determine UK cat owners' attitudes towards surgical treatments of different anatomical regions. METHODS A cross‐sectional study of an anonymous convenience sample of UK cat owners was conducted from September to December, 2012 using an internet‐based survey. RESULTS There were a total of 208 respondents: 39% would pursue surgery regardless of tumour site. One percent would not pursue surgery. Of the remainder, respondents would not allow amputation of the forelimb (20%), hindlimb (15%) or tail (15%). Twenty‐six, 32 and 27% would not have surgical treatment of the inter‐scapular region, chest or abdomen, respectively. The majority of respondents were willing to travel up to 100 miles for radiotherapy or chemotherapy (66 and 69%, respectively). CLINICAL SIGNIFICANCE The current feline vaccine site recommendations may not be appropriate for UK cat owners.